Comparison of English, German and Uzbek Vowel Sounds - Zulfiyaxon Masodiqova; Zarnigorxon Meliqo'ziyeva Ikromjon qizi (Research Parks Publishers, 2021)
This research work shows the differences and similarities of vowel sound system in three languages: English, German and Uzbek. There are vowels sounds in any language, but their number is not equal. According to the family of the languages there are some similirities, such as English and German belong to Indo-Europian languages and their phonetic system has the same structures. However, Uzbek is from Turkic languages and it totally differs from English and German